Limited expression of TLR9 on T cells and its functional consequences in patients with nonalcoholic fatty liver disease - Alegre, Nadia Soledad (2019)
We demonstrated a limited expression of Toll-like receptor 9 (TLR9) and interferon gamma (IFN-γ) production by T cells in patients with simple steatosis (SS). The limited expression of TLR9 on T cells was directly associated with lower liver necroinflammatory activity and fibrosis, and lower antrophometric and biochemical alterations of nonalcoholic fatty liver disease. Besides, co-stimulation of T cell activation via TLR9 induced a limited number of IFN-γ-producing CD8+ T cells in SS patients. Accordingly, these patients showed a low frequency of circulating type 1 CD8+ cells whereas additional pro-inflammatory signals may be responsible for the higher frequency observed at baseline in the context of steatohepatitis.